Rituximab: a novel treatment for refractory Riedel's thyroiditis. (9th February 2018) - Hunt, Leanne; Harrison, Barney; Bull, Matthew; Stephenson, Tim; Allahabadia, Amit
Summary: This case report reviews the rare condition of Riedel's thyroiditis via a patient case. The report highlights the difficulties that one may encounter when managing such a case in regards to patient symptoms, side effects of medications and the relapsing nature of the condition. The case report also highlights novel treatment in the treatment of Riedel's thyroiditis, rituximab, how this works and the resolution of symptoms that we have achieved with our patient on this treatment. Learning points: Riedel's thyroiditis is characterised by chronic inflammation, which causes dense fibrosis in the thyroid gland. Riedel's thyroiditis can present with neck pain, dysphagia and dyspnoea with a firm, non-tender mass found on examination. Riedel's thyroiditis is part of the IgG4-related systemic disorders. Rituximab is a monoclonal antibody that works against the protein CD20.